Analysis of Digital-Based Elementary School Learning Assessment Applications - Balqis Fauzatul Rohmah; Choirul Anam (Yayasan Avicenna, 2023)
This study aims to analyze in depth the implementation of digital-based learning assessment applications at the Elementary School level, including conceptual understanding, implementation practices, and obstacles faced. The method used is library research with a qualitative approach, where data is collected from various literature sources such as books, scientific journals, and related educational documents. The results of the study indicate that digital assessment applications such as Google Form, ProProfs, and Quizizz are able to facilitate the evaluation process more effectively, efficiently, and interestingly for students. These applications can measure various aspects of student competence—namely attitudes, knowledge, and skills—systematically, both in face-to-face and online learning conditions. However, technical obstacles such as limited devices, internet connections, and students' digital competence are the main challenges in its implementation. The implications of these findings emphasize the importance of improving digital literacy for teachers and students, as well as supporting educational infrastructure to support the successful use of technology in learning evaluation.